Livelihood assets financing as a CSR initiative of microfinance banks in Nigeria - Adewale, Abideen Adeyemi (Gower Publishing Limited, 2014)
The objective of this chapter is to provide a theoretical model that accentuates the imperatives of Nigerian microfinancial institutions’ corporate social responsibility (CSR) activities aimed at ensuring that access to and use of financial services are maximized by the unbanked. Based on the extant literature, this chapter demonstrates that enormous opportunities that transcend philanthropy exist through which the Nigerian microfinance banks can be socially responsible. The conclusion and recommendation offered elicit the need for empirical studies that investigate the implications of the apparent social mission drift of the Nigerian microfinance banks for the accumulation of the requisite livelihood assets needed by the poor for a sustainable livelihood